Jenis Intervensi dalam Meningkatkan Kepuasan Kerja Perawat - Arniawan Arniawan; Nur Setiawati Dewi; Septo Pawelas Arso (Journal of Telenursing (JOTING), 2023)
This study aims to determine the types of interventions that can increase the job satisfaction of nurses in hospitals through an article review approach. The research method used is scoping review through databases namely Pubmed, ScienceDirect, Scopus, SpringerLink, and Garuda Portal. The results of the study show that 15 interventions articles that can increase nurse job satisfaction include organizational culture, organizational commitment, implementation of nurse welfare programs, work professionalism, clinical supervision, implementation of sharia behavior in nursing services, scheduling management, leadership, democratic leadership, transformational leadership, style transformational leadership, organizational climate, application of the team method, application of the professional nursing practice model (MPKP), leadership style, and structural empowerment. In conclusion, this type of intervention is proven to increase the nurses job satisfaction. Keywords: Intervention, Job Satisfaction, Nurse